2022
DOI: 10.1186/s12891-022-05129-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of monoplanar and polyaxial screw fixation systems in percutaneous intermediate fixation for thoracolumbar fractures

Abstract: Background The newly developed monoplanar pedicle screws (MPPSs) can mobile in axial plane but fixed in the sagittal plane, which holds potential to combine ease of rod placement with sagittal plane strength theoretically. So far, few clinical studies focused on the outcomes of MPPSs for treatment of thoracolumbar fractures (TLFs). The aim of this study was to compare the efficacy of MPPSs to polyaxial pedicle screws (PAPSs) in percutaneous intermediate fixation of TLFs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The other is that intermediate fixation with MS that were inserted parallel to the upper endplate of the injured vertebra can circumvent the anterior vertebral fracture regions and use relatively longer screws, allowing better restoration of the anterior vertebral height and the upper endplate of the injured vertebra. Similarly, a clinical study by Huang et al [ 37 ] indicated that MSs fixation achieved better correction effect and less correction loss than polyaxial screw fixation alone. According to Ye et al [ 38 ] MS probably a superior option to reduce the incidence of degeneration of the injured vertebral adjacent segment than fixed axial screw.…”
Section: Discussionmentioning
confidence: 93%
“…The other is that intermediate fixation with MS that were inserted parallel to the upper endplate of the injured vertebra can circumvent the anterior vertebral fracture regions and use relatively longer screws, allowing better restoration of the anterior vertebral height and the upper endplate of the injured vertebra. Similarly, a clinical study by Huang et al [ 37 ] indicated that MSs fixation achieved better correction effect and less correction loss than polyaxial screw fixation alone. According to Ye et al [ 38 ] MS probably a superior option to reduce the incidence of degeneration of the injured vertebral adjacent segment than fixed axial screw.…”
Section: Discussionmentioning
confidence: 93%